Genetic Analysis and Mapping of QTLs for Soybean Biological Nitrogen Fixation Traits Under Varied Field Conditions - Yang, Qing; Yang, Yongqing; Xu, Ruineng; Lv, Huiyong; Liao, Hong (Frontiers in Plant Science, 2019)
Soybean is an important economic and green manure crop that is widely used in intercropping and rotation systems due to its high biological nitrogen fixation (BNF) capacity and the resulting reduction in N fertilization. However, the genetic mechanisms underlying soybean BNF are largely unknown. Here, two soybean parent genotypes contrasting in BNF traits and 168 F9:11 recombinant inbred lines (RILs) were evaluated under four conditions in the field. The parent FC1 always produced more big nodules, yet fewer nodules in total than the parent FC2 in the field. Furthermore, nodulation in FC1 was more responsive to environmental changes than that in FC2. Broad-sense heritability (h2b) for all BNF traits varied from 0.48 to 0.87, which suggests that variation in the observed BNF traits was primarily determined by genotype. Moreover, two new QTLs for BNF traits, qBNF-16 and qBNF-17, were identified in this study. The qBNF-16 locus was detected under all of the four tested conditions, where it explained 15.9%-59.0% of phenotypic variation with LOD values of 6.31-32.5. Meanwhile qBNF-17 explained 12.6-18.6% of observed variation with LOD values of 4.93-7.51. Genotype group analysis indicated that the FC1 genotype of qBNF-16 primarily affected nodule size (NS), while the FC2 genotype of qBNF-16 promoted nodule number (NN). On the other hand, the FC1 genotype of qBNF-17 influenced NN and the FC2 genotype of qBNF-17 impacted NS. The results on the whole suggest that these two QTLs might be valuable markers for breeding elite soybean varieties with high BNF capacities.